Layanan Bimbingan Kelompok untuk Meningkatkan Self-Esteem Siswa - Dachmiati, Sabrina; Amalia, Rizki (JURNAL FOKUS KONSELING, 2017)
Abstract: The purpose of this study is to test the effectiveness of group guidance in improving students self-esteem SMAN 1 Cariu Bogor. The research method used is quantitative method with quasi-experiment approach. The study population was 148 students of class X. Samples taken by using sample quota samples were 16 students, divided into two groups; experimental groups and control groups. Self-esteem instruments are used to find out the students self-esteem level by 20 items. Data analysis techniques using percentage of questionnaire results. The conclusion of this research is the effective group counseling service in improving students self-esteem.Keywords: guidance group, self-esteem.